THE PHILOSOPHY AND CONCEPT OF THE LOVE CURRICULUM IN EDUCATION: A LITERATURE REVIEW ON INSTILLING THE VALUES OF LOVE, EMPATHY, TOLERANCE, AND HARMONY BASED ON ISLAMIC EDUCATION, HUMANISM, AND THE THEORY OF LOVE - ELMIWATI ELMIWATI; Aslan Aslan (International Journal of Teaching and Learning, 2025)
This study aims to describe the philosophy and concept of the love curriculum in the context of education, with a focus on instilling the values of love, empathy, tolerance, and harmony. The study was conducted through a literature review that integrated the perspectives of Islamic education, humanism, and the theory of love from educational psychology. The results of the study show that the love curriculum is an educational paradigm that balances spiritual, ethical, and emotional dimensions in the learning process. Islamic education provides a normative foundation through the teachings of rahmatan lil 'alamin, humanism emphasises respect for human dignity, while the theory of love emphasises the development of empathy as a skill that can be honed. The implementation of these values in the curriculum is expected to produce a generation that is not only intellectually intelligent, but also emotionally and socially mature, and capable of building a harmonious society. This study concludes that the love curriculum can be a strategic alternative in facing educational challenges in the modern era.